PENGENDALIAN KUALITAS PRODUK KAIN GREIGE DENGAN METODE QUALITY CONTROL CIRCLE DI PT. APAC INTI CORPORA - Marsya Shadrina (2022)
As a company engaged in the textile industry, quality control is one of the crucial things that deserves attention by PT. Apac Inti Corpora to maintain product quality in order to meet their customer satisfaction. This study aims to identify the most dominant type of defect, find out the factors that cause defects, model the relationship between factors that cause defect and the defect it self, as well as ways to minimize the occurrence of defect. In this study the Quality Control Circle method was used with the PDCA approach (plan, do, check, action) and it was found that the most dominant type of defect was filling bar with a value of 14.1%. It is also known that the factors that cause defects are machine, material, method, and human factors with the factor that has the greatest influence is the machine factor, and a multiple linear regression model is also obtained which has the equation Y = 3.129 + 0.419 X1 + 0.226 X2 + 0.169 X3 + 0.310 X4 + e with an R Square value of 0.864. The way to minimize the occurrence of defects in the filling bar type is by replacing worn-out machine spare parts and scheduling a routine machine maintenance, checking periodically as well as re-setting machine, and updating the old machines.